2023
DOI: 10.3904/kjim.2022.348
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an abnormal ankle-brachial index on ischemic and bleeding events in patients undergoing percutaneous coronary intervention

Abstract: Background/Aims: Bleeding events after percutaneous coronary intervention (PCI) have important prognostic implications. Data on the influence of an abnormal ankle-brachial index (ABI) on both ischemic and bleeding events in patients undergoing PCI are limited.Methods: We included patients who underwent PCI with available ABI data (abnormal ABI, ≤ 0.9 or > 1.4). The primary endpoint was the composite of all-cause death, myocardial infarction (MI), stroke, and major bleeding.Results: Among 4,747 patients, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…To better understand the underlying pathophysiology of the relationship between ABI and CAD, more research is needed, using advanced imaging techniques or biomarker analysis to assess the roles of inflammation, oxidative stress, and other mechanisms in the development of both conditions. Kim et al [6] did not study the effec-tive of intervention to improve ABI in patients with CAD. It would be valuable to compare different interventions such as exercise, medication, and revascularization to determine the most effective approach for improving ABI and reducing cardiovascular risk in this patient population.…”
Section: See Article On Page 372-381mentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the underlying pathophysiology of the relationship between ABI and CAD, more research is needed, using advanced imaging techniques or biomarker analysis to assess the roles of inflammation, oxidative stress, and other mechanisms in the development of both conditions. Kim et al [6] did not study the effec-tive of intervention to improve ABI in patients with CAD. It would be valuable to compare different interventions such as exercise, medication, and revascularization to determine the most effective approach for improving ABI and reducing cardiovascular risk in this patient population.…”
Section: See Article On Page 372-381mentioning
confidence: 99%
“…Although patients with CAD and concomitant PAD have been considered as a high-risk subgroup with a greater incidence of adverse ischemic events after PCI, few data exist regarding the clinical utility of the ABI for predicting bleeding complications, which affects the outcome. Kim et al [6] showed that an abnormal ABI was associated with a higher incidence of all-cause mortality, recurrent myocardial infarction, and major bleeding events over a 5-year period. An abnormal ABI was an independent risk factor for major bleeding in the multivariate analysis.…”
mentioning
confidence: 99%